2020
DOI: 10.3390/su12114568
|View full text |Cite
|
Sign up to set email alerts
|

University as Change Manager of Attitudes towards Environment (The Importance of Environmental Education)

Abstract: The university is an essential participant in education, a key place where societal change processes are developed. So, it must be a place to bring up current challenges and social requirements. That is the reason why it holds the responsibility to assure the creation of knowledge, skills, attitudes, and values in the students to achieve an effective solution to environmental issues. The objective of this research was the assessment of the attitudes, knowledge, and pro-environmental behavior in university stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 42 publications
0
12
0
1
Order By: Relevance
“…In the context of development of teaching strategies, it should be pointed out that the occurrence of an environmental component in terms of the job positions performed by students during their work placement (n = 3680) is not influenced by gender or the form of study (full-time and combined). The impact of gender contradicts the studies of Ibáñez et al and Schönfelder et al [18,19] that highlight the importance of gender differences in environmental education. This result may be due to the uneven representation of women and men in our sample, as well as cultural differences.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In the context of development of teaching strategies, it should be pointed out that the occurrence of an environmental component in terms of the job positions performed by students during their work placement (n = 3680) is not influenced by gender or the form of study (full-time and combined). The impact of gender contradicts the studies of Ibáñez et al and Schönfelder et al [18,19] that highlight the importance of gender differences in environmental education. This result may be due to the uneven representation of women and men in our sample, as well as cultural differences.…”
Section: Discussionmentioning
confidence: 79%
“…Gender differences were also addressed by Ibáñez et al [18] in a study which aimed to analyse and evaluate the attitudes, knowledge and environmental behaviour of university students of various faculties, study programmes and higher education levels. The results have shown that most of the students believe that a quality environmental education is necessary for solving the environmental problems that affect them.…”
Section: Ethical Commitmentmentioning
confidence: 99%
“…Both EE and ESD are forms of education that are openly committed to a cause and to transformative action [6,7,17,23]. For this, they have been criticized by some.…”
Section: Esd and The Danger Of Indoctrinationmentioning
confidence: 99%
“…Therefore, environmental education should be a lifelong endeavor for individuals who wish to make positive contributions to the present and future of the environment. When we talk about environmental education, we are referring to the process of providing students with knowledge, skills, attitudes, and values about the environment and the problems that it faces (Pandey & Wright, 2006;Esteban -Ibanez et al, 2020).…”
Section: Introductionmentioning
confidence: 99%